Reasons For Criminal Disinheritance - Hatice Kübra Ercoşkun Şenol (İstanbul Hukuk Mecmuası)
Article 510 of the Turkish Civil Code outlines the grounds for disinheritance. If an heir with a reserved share commits a grave crime against the legator or one of his relatives, the legator may remove this heir from the inheritance through a disposition mortis causa. Furthermore, if the heir with the reserved share does not fulfill his/her obligations arising from family law against legator or his/her family members substantially, the legator can remove this heir from the inheritance through disposition mortis causa. However, neither the article in question nor its preamble specify who is considered a relative or family member of the legator or which crimes fall within the scope of a serious offense. Moreover, what should be understood from the significant nonfulfillment of the obligations arising from family law is not specified. As the judicial decisions on the subject contradict each other, the views on the doctrine related to the subject are different. However, nowadays, it is observed that the tendency to recognize superiority to the will of the legator is becoming stronger. In the controversy of disinheritance for criminal reasons that are not regulated explicitly in the law, the interpretation that recognizes superiority to the will of the legator should always be given priority. Article 511 of the Turkish Civil Code specifies the repercussions of disinheritance for criminal reasons. The reason for disinheritance must be stated in the disposition mortis causa for these provisions and outcomes to take effect. Otherwise, according to Article 512 of the Turkish Civil Code, the disposition is executed with the exception of the heir’s reserved share. Moreover, according to this provision, the disposition mortis causa is carried out other than the reserved share of the heir if the existence of the reason for disinheritance cannot be proven by the heirs benefiting from the disinheritance. However, if the legator makes an error regarding the reason for the disinheritance, the heir with the reserved share can take the entire inheritance share by proving that the legator made a mistake. There are also various provisions and consequences created by the disinheritance for criminal or similar reasons, both within and outside the law of inheritance.